2022
DOI: 10.1108/jeim-10-2020-0422
|View full text |Cite
|
Sign up to set email alerts
|

Assessing organizational health-analytics readiness: artifacts based on elaborated action design method

Abstract: PurposeWhile the adoption of health-analytics (HA) is expanding, not every healthcare organization understands the factors impacting its readiness for HA. An assessment of HA-readiness helps guide organizational strategy and the realization of business value. Past research on HA has not included a comprehensive set of readiness-factors and assessment methods. This study’s objective is to design artifacts to assess the HA-readiness of hospitals.Design/methodology/approachThe information-systems (IS) theory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Literature has widely discussed innovation resistance theory (IRT) in this regard and observed high resistance from users to adopt a new service (Kamal, 2006, Kaur et al ., 2020a, b; Haddara et al ., 2022; Iyanna et al ., 2022). The unwillingness of doctors or medical staff to the adoption of tech services is high, as they believe that technology would promote data-led decision-making (Venkatraman and Sundarraj, 2023). Implementation of digital technologies has a high impact on internal organizational resources, such as employees (Almansour, 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Literature has widely discussed innovation resistance theory (IRT) in this regard and observed high resistance from users to adopt a new service (Kamal, 2006, Kaur et al ., 2020a, b; Haddara et al ., 2022; Iyanna et al ., 2022). The unwillingness of doctors or medical staff to the adoption of tech services is high, as they believe that technology would promote data-led decision-making (Venkatraman and Sundarraj, 2023). Implementation of digital technologies has a high impact on internal organizational resources, such as employees (Almansour, 2023).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Active barriers are associated with changes in value, risk and usage towards a new service. Passive barriers, also known as psychological barriers, arise when a user's perception is not aligned with a new service (Venkatraman and Sundarraj, 2023). Both barriers enhance future business uncertainties (Haddara et al ., 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…used eADR to diagnose, design, and implement automated systems for the repeatable synthesis of data into insights that aided daily, weekly, and monthly decision-making by creating artefacts such as data sets, guidelines, decision trees, and dashboards, and found that the eADR provided a significant benefit in its focus on the abstraction and evaluation of artefacts during fast, flexible, iterative investigation efforts. Venkatraman and Sundarraj (2022) also had a problem-centred entry point, eventually creating three artefacts to assess the healthcare analytics readiness of hospitals. Due to limitations after the design of their pilot artefact, they required a deeper understanding of the problem space with a broader set of cases and more hospitals.…”
Section: Applications Of Eadrmentioning
confidence: 99%